2011
DOI: 10.2169/internalmedicine.50.5942
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Performance Index in Subjects Susceptible to High-Altitude Pulmonary Edema

Abstract: Objective A recent study concerning high-altitude pulmonary edema (HAPE), a non-cardiogenic pulmonary edema, suggested that it is initially a hydrostatic-type pulmonary edema. We suspect that some extent of cardiac insufficiency may likely relate to the mechanism of the development of this disease. Methods By Doppler echocardiography, the Tei index (a new quantitative index proposed for the evaluation of global myocardial performance) and the systolic pulmonary artery pressure (sPAP) were measured before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Data regarding the effect of acute high-altitude exposure on RV function and structure are sparse and conflicting. While some studies report that an acute hypoxia-induced increase in RV afterload leads to an improved contractility [17], others found no change [18] or even an impaired contractility [19][20][21]. The discrepancies in the existing literature could be related to the considerable differences between methods and research designs.…”
Section: Discussionmentioning
confidence: 97%
“…Data regarding the effect of acute high-altitude exposure on RV function and structure are sparse and conflicting. While some studies report that an acute hypoxia-induced increase in RV afterload leads to an improved contractility [17], others found no change [18] or even an impaired contractility [19][20][21]. The discrepancies in the existing literature could be related to the considerable differences between methods and research designs.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been suspected that some extent of cardiac insuffi ciency may favour the development of HAPE. The Tei index of RV function measured by Doppler echocardiography before and after 30 min of hypoxic breathing in 11 HAPE-susceptible subjects compared to nine HAPE-resistant subjects evidenced an enhanced left ventricular myocardial performance but an impaired right ventricular performance in HAPEsusceptible subjects [ 21 ]. Elite swimmers following a "Living High Training Low" procedure during 13 days between 2,500 and 300 simulated altitude showed a slight increase in the RV/LV diameters ratio at echocardiography, suggesting a slight dilatation of the right ventricle without alteration of contractile function [ 22 ].…”
Section: Acute Exposure Of Sea Level (Sl) Natives Normal Subjectsmentioning
confidence: 88%
“…This is in keeping with previous findings that suggested that LV systolic function was improved in hypoxic healthy volunteers [ 1 – 3 , 22 , 23 ] and even in studies referring to adults and children exposed to high altitude [ 21 , 24 ]. The improved cardiac systolic function in hypoxic environments allows for the output of the maximum amount of blood to transfer a sufficient amount of oxygen to support the metabolic demands of a body challenged by hypoxic stress [ 9 ]. As expected, the present data did show an improvement in cardiac output in all subjects, due to their elevated HR and SV.…”
Section: Discussionmentioning
confidence: 99%